Encyclopedia of contemporary Spanish culture - Rodgers, E. J. (Eamonn J.) (Encyclopedias of contemporary culture series., 1999)
Some 750 alphabetically-arranged entries provide insights into recent cultural and political developments within Spain, including the cultures of Catalonia, Galicia and the Basque country. Coverage spans from the end of the Civil War in 1939 to the present day, with emphasis on the changes following the demise of the Franco dictatorship in 1975. Entries range from shorter, factual articles to longer overview essays offering in-depth treatment of major issues. Culture is defined in its broadest sense. Entries include:*Antonio Gaudí * science * Antonio Banderas * golf * da.